2021
DOI: 10.1021/acs.jmedchem.0c01984
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Constraint between Aromatic Residue Side Chains in the “Message” Sequence of the Peptide Arodyn Using Ring Closing Metathesis Results in a Potent and Selective Kappa Opioid Receptor Antagonist

Abstract: Kappa opioid receptor (KOR) antagonists have recently shown potential for treating drug addiction and mood disorders. The linear acetylated dynorphin A analog arodyn (Ac­[Phe1,2,3,Arg4,d-Ala8]­dynorphin A-(1–11)­NH2), synthesized in our laboratory, demonstrated potent and selective KOR antagonism. Cyclization of arodyn could potentially stabilize the bioactive conformation and enhance its metabolic stability. The cyclization strategy employed involved ring closing metathesis between adjacent meta- or para-subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…The data demonstrated that the optimized configuration for 1 and 5 was cis and trans , respectively, indicating that stapled peptides with different ring sizes have different optimized conformations. This result was also observed in other opioid-stapled peptides, including cyclic enkephalin and dynorphin. …”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The data demonstrated that the optimized configuration for 1 and 5 was cis and trans , respectively, indicating that stapled peptides with different ring sizes have different optimized conformations. This result was also observed in other opioid-stapled peptides, including cyclic enkephalin and dynorphin. …”
Section: Discussionsupporting
confidence: 59%
“…One study on antimicrobial peptides has shown that disulfide cyclized peptide exhibited 4.5-fold increased stability compared to linear peptide, while all-hydrocarbon stapled peptide exhibit a 70-fold increase . However, there are only a few reports on the application of all-hydrocarbon stapled in opioid peptides, and these studies have been limited to in vitro activity evaluations. These studies have demonstrated that the agonistic activities of enkephalin on the MOPr and delta-opioid receptor (DOPr), as well as dynorphin on the kappa-opioid receptor (KOR), remain unchanged or slightly increased after all-hydrocarbon stapled modification.…”
Section: Introductionmentioning
confidence: 99%
“…Local conformational constraints have been introduced into peptides for many years by straightforward chemical approaches, and constitute a productive strategy for increasing the target affinity and stability of peptides of medicinal interest. [25][26][27] In comparison, the preparation of proteins containing localized residues that are constrained conformationally is more problematic from a technical perspective. In the past few years, we have described a new method for modifying bacterial ribosomes, and selecting ribosomes that recognize suppressor tRNAs activated with dipeptides and dipeptidomimetics, enabling the introduction of modified residues within proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Biologically active peptides have long been modified with conformationally constrained motifs to improve their binding affinity and metabolic stability. [25][26][27] In comparison, there has been no reported study of enzyme function by incorporating a conformationally constrained dipeptide at a specific protein position. Our laboratory has developed a dual selection procedure to obtain a set of modified ribosomes able to carry out protein synthesis with a variety of non-canonical amino acids, including conformationally constrained dipeptides.…”
Section: Introductionmentioning
confidence: 99%
“…The amide bond is one of the most important and fascinating functional groups in organic chemistry and biochemistry owing to its widespread occurrence in natural products, peptides, proteins, and a plethora of other biomolecules [1,2]. Medicinally, the amide-forming reactions are pivotal in the pharmaceutical industry and medicinal chemistry for the preparation of active pharmaceutical ingredients [3,4], insecticides [5,6], polymers [7], and a vast number of bioactive molecules [8][9][10][11][12]. Most notably, the amide functional group is present in approximately a quarter of clinically approved drugs and two-thirds of all drug candidates [13].…”
Section: Introductionmentioning
confidence: 99%